2008
DOI: 10.1121/1.2908198
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism stimulating sound production from air bubbles released from a nozzle

Abstract: Gas bubbles in water act as oscillators with a natural frequency inversely proportional to their radius and a quality factor determined by thermal, radiation, and viscous losses. The linear dynamics of spherical bubbles are well understood, but the excitation mechanism leading to sound production at the moment of bubble creation has been the subject of speculation. Experiments and models presented here show that sound from bubbles released from a nozzle can be excited by the rapid decrease in volume accompanyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…At any given bubble radius measured, there was around an order of magnitude of scatter in values of R 30i /R 0 . They conclusively identified the mechanism for bubble excitation for the shear fragmentation they measured (which would probably resemble excitation during injection or underwater gas pipe leakages) as a volume change in the bubble gas generated by the rupture of the necking region between the future fragments, the energy being manifest at the moment of fragmentation in the surface tension energy associated with the geometry of the neck (Deane & Czerski 2008;Deane & Stokes 2008). Importantly, they predicted that the forcing function was proportional to the internal gas pressure in the bubble, suggesting the possibility that for a given bubble radius the quantity R 30i /R 0 may be broadly invariant with depth (within the limits of the observed scatter, over much of the bubble size range).…”
Section: The Forward Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…At any given bubble radius measured, there was around an order of magnitude of scatter in values of R 30i /R 0 . They conclusively identified the mechanism for bubble excitation for the shear fragmentation they measured (which would probably resemble excitation during injection or underwater gas pipe leakages) as a volume change in the bubble gas generated by the rupture of the necking region between the future fragments, the energy being manifest at the moment of fragmentation in the surface tension energy associated with the geometry of the neck (Deane & Czerski 2008;Deane & Stokes 2008). Importantly, they predicted that the forcing function was proportional to the internal gas pressure in the bubble, suggesting the possibility that for a given bubble radius the quantity R 30i /R 0 may be broadly invariant with depth (within the limits of the observed scatter, over much of the bubble size range).…”
Section: The Forward Problemmentioning
confidence: 99%
“…, where G is a ring-up factor evaluated by empirical observation or from the developing theoretical base (Longuet-Higgins 1990;Pumphrey & Ffowcs Williams 1990;Leighton 1994, §3.7.3;Clarke & Leighton 2000;Deane & Czerski 2008). Substitution of (2.5) into (2.3) gives the monopole emission detected in the far field from a single bubble:…”
Section: The Forward Problemmentioning
confidence: 99%
“…Recent research 4 has shown that the sound emitted when a new bubble is formed at a nozzle is consistent with the volume forcing produced by the rapid change in bubble shape just after pinch-off. The collapse of the conical neck of air that had connected the new bubble to the parent gas supply is fast because the radius of curvature of the new surface is very small.…”
Section: Introductionmentioning
confidence: 94%
“…(9) is due to the form in which the forcing is inserted into the Rayleigh-Plesset equation, as an equivalent external pressure. 4 This forcing term can then be used to drive the linearized Rayleigh-Plesset equation, once the appropriate time dependence is taken into account (discussed below). To apply the Rayleigh-Plesset equation, it is necessary to use an equivalent spherical radius for the new bubble, and we assume here that the breathing mode response of the bubble can be described using spherical symmetry.…”
Section: Dynamical Modelmentioning
confidence: 99%
See 1 more Smart Citation